Ternate Government’s Efforts in Establishing Culture-based Tourism Destinations through Heritage City - Nurlaili, Nurlaili; Nursiana, Adinoto; Hermantoro, Henky (Jurnal Penelitian Pariwisata, 2017)
Ternate, one of the oldest cities in Indonesia, has committed to establish a culture-based tourism through heritage city. This city needs to go through some approaches by conducting inventory of historical studies and mapping the existing historical assets. To achieve the goals above, the history of the city can provide distinctiveness on the theme of the city as heritage-based coastal and islands. This research aims to find out the efforts conducted by the local government to create the heritage city as part of culture-based tourism. The method used in this research is the mixed methods which combines qualitative and quantitative. The research is done by combining two forms of pre-existing research which emphasizes on the understanding of problems in social life based on reality on natural setting. The research has revealed some attempts from the local government to increase the value of assets heritage and also to restore the glory of Ternate in the future simultaneously. And these efforts, have gained full support from the local community